PENDAPATAN USAHATANI PADI SAWAH DI DESA MAPANGET KECAMATAN TALAWAAN MINAHASA UTARA - Miske Eva Ollo; Caroline B. D. Pakasi; Celcius ., Talumingan (AGRI-SOSIOEKONOMI, 2018)
This study aims to determine the income of farmers from rice field farms in the Mapanget Village Talawaan Sub-district North Minahasa. This study lasted for 3 (three) months from the preparation stage, data retrieval and to the preparation of research. Research location in Mapanget Village, Talawaan Sub-district, North Minahasa. Primary data is obtained through a list of questions that have been prepared, while secondary data obtained from the district office and village office. Based on the research results, the income of paddy field farming managed by respondents in Mapanget village comes from harvest season 1 (one), harvest season 2 (two) and harvest season 3 (three). Wetland paddy farming in Mapanget Village is able to provide benefits and the farming continues to be cultivated even in urban areas.*er*.